Chromosomal Aneuploidy Associated With Clinical Characteristics of Pregnancy Loss - Gu, Chongjuan; Li, Kuanrong; Li, Ru; Li, Ling; Li, Xiaojun; Dai, Xinyu; He, Yaojuan (Frontiers in Genetics, 2021)
Objective: Embryonic aneuploidy are found in about half of sporadic pregnancy loss and the associations between the chromosomal aneuploidy and clinical characteristics of pregnancy loss remain unclear. The aims of this study were to evaluate the associations between chromosomal aneuploidy of products of conception (POC) with clinical features of pregnancy loss, including the maternal age, history of pregnancy loss and the ultrasound findings. Methods: We conducted a retrospective cohort study including 1102 women experienced singleton pregnancy loss and underwent chromosomal microarray analysis (CMA) detection of POC in our hospital. The results of chromosomal karyotype and clinical features including maternal age, history of pregnancy loss, gestational age, vaginal bleeding and ultrasonographic findings were extracted from the medical records. χ2 test was used to compare categorical data between groups. Results: 631 (57.26%) POC specimens were detected to be chromosomal aneuploidy. Aneuploid rate was significantly increased in women ＞35 years (P <0.001) and pregnancy loss <11 gestational weeks (P=0.044), but the rates of sex chromosomal abnormality and triploid were significantly high in women ≤35 years (P＜0.001, P=0.002) and the rates of viable autosomal trisomy and sex chromosome abnormal were significantly high in those with pregnancy loss ≥11 weeks（P <0.001, P <0.001). Aneuploid rate was overall similar between the sporadic and the recurrent pregnancy loss (P=0.404), but sex chromosomal abnormality rate was increased in women with sporadic pregnancy loss (P=0.03). Aneuploid rates were higher in subjects with yolk sac or embryo than in those without (P<0.001, P=0.001). Conclusion: Advanced maternal age mainly relates to increased autosomal trisomy, while sex chromosome abnormal and triploid might more likely occur in younger women. Aneuploidy rates might have no association with previous pregnancy loss except for sex chromosome abnormal. Pregnancy loss without yolk sac or embryo might be less relative to embryonic aneuploidy, and other factors should be emphasized.